Analisis Hubungan Gaya Kepemimpinan dan Motivasi dengan Kinerja Pegawai RumahSakit Bhayangkara Tk. I Raden Said Sukanto Jakarta - Lestari, Bella Sarwestri; Wigati, Putri Asmita; Arso, Septo Pawelas (Fakultas Kesehatan Masyarakat, 2015)
Key factor successful of an institution especially hospital is Human Resources. Human resources referred to medical support (doctor and nurse), general support and administrative officer. Hospital very important to create quality human resources, have skills and highly capable. Therefore the passage of the process of Public Services Agencies in hospital of Bhayangkara 1st Level Raden Said Sukanto Jakarta surely need high quality from human resources itself in terms of proficiency and mental attitude. The leader with background as a police and background of employees as a government employee create motivation and different leadership style which perceived by employee that could create different work performance from another government hospital. Purpose of this research was knowing relation between leadership style and motivation with performance of employees Bhayangkara hospital 1st level Raden Said Sukanto Jakarta. This research was quantitative research with cross sectional measuring by questionnaire. Population of this research all of government employees and police member who works part bottom line managers in staffing structure of Bhayangkara hospital 1st level Raden Said Sukanto Jakarta. Sampling of this research by using random sampling technique total 80 respondents from 400 employees.Bivariat analysis by using chi square test. Result of bivariat analysis shows that there is a relation between leadership style (p= 0,006) and motivation (p=0,001) with performance employees Bhayangkara hospital 1st level Raden Said Sukanto Jakarta. Recommendation for Bhayangkara hospital 1st level Raden Said Sukanto Jakarta to do an evaluation employees performance objectively so that will show achievement from employees and make two ways communication between leader with employee to push ahead employee motivation at work.